Predictors of behaviour in solitary fibrous tumours of the pleura surgically resected: Analysis of 107 patients. Issue 4 (16th July 2019) - Bellini, Alice; Marulli, Giuseppe; Breda, Cristiano; Ferrigno, Pia; Terzi, Stefano; Lomangino, Ivan; Lo Giudice, Fabio; Brombin, Claudia; Laurino, Licia; Pezzuto, Federica; Calabrese, Fiorella; Rea, Federico
Abstract: Objectives: Gold standard therapy for solitary fibrous tumour of the pleura is complete surgical resection. Aims of this retrospective study are to evaluate oncological and surgical outcomes and to verify the clinical reliability of prognostic scores presented in literature. Methods: Study population: 107 patients surgically treated between 1972 and 2018. Male/female ratio: 1/2.45; median age at surgery: 60 years (range, 19‐80); peduncle lesions 69.8%; visceral pleura origin 72.9%; benign histology 73.8%; median diameter 8 cm (range 1 to 35, 27 cases giant [≥15 cm]). Results: After a median follow up of 7 years, 12 patients had recurrence. By multivariate analysis, malignant histology ( P = .03; HR, 4.17; 95% CI, 1.15‐15.06), origin from parietal pleura ( P = .03; HR, 3.90; 95% CI, 1.08‐14.09), England ( P = .002; HR, 1.98; 95% CI, 1.28‐3.07), Diebold ( P = .008; HR, 1.96; 95% CI, 1.20‐3.22) and Tapias ( P = .003; HR, 1.75; 95% CI, 1.20‐2.53) scores were found independent significant predictors of relapse. Giant tumours were associated with open surgery ( P = .003), origin from parietal pleura ( P = .011) and intraoperative bleeding ( P > .001). Overall 10‐year disease‐free survival (DFS) rate was 81%. Predictors of worst DFS were parietal pleura origin ( P = .002), malignant histology ( P = .006) and all the prognostic scores. Conclusions: Malignant histology and origin from parietal pleura were significant predictors of tumour recurrence and worst DFS. The use of current scoring systems can help to predict clinical behaviour. Patients with higher risk of relapse can benefit from closer follow up, prolonged over 10 years.